2022
DOI: 10.1021/acs.est.1c05915
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effects of Silver Nanoparticles on Development, Behavior, and Mitochondrial Function are Altered by Genetic Defects in Mitochondrial Dynamics

Abstract: Silver nanoparticles (AgNPs) are extensively used in consumer products and biomedical applications, thus guaranteeing both environmental and human exposures. Despite extensive research addressing AgNP safety, there are still major knowledge gaps regarding AgNP toxicity mechanisms, particularly in whole organisms. Mitochondrial dysfunction is frequently described as an important cytotoxicity mechanism for AgNPs; however, it is still unclear if mitochondria are the direct targets of AgNPs. To test this, we expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 72 publications
(113 reference statements)
1
9
0
Order By: Relevance
“…The levels of ATP and ADP metabolism, key metabolites shared by OXPHOS, glycolysis, and the TCA cycle, did not change significantly in all tested groups (Figures S13E,L). ATP and ADP were measured based on steady-state levels, rather than ADP phosphorylation . However, the compensatory mechanism of mitochondrial respiration may allow for regulating ATP production and use by bypassing the inhibition of OXPHOS .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of ATP and ADP metabolism, key metabolites shared by OXPHOS, glycolysis, and the TCA cycle, did not change significantly in all tested groups (Figures S13E,L). ATP and ADP were measured based on steady-state levels, rather than ADP phosphorylation . However, the compensatory mechanism of mitochondrial respiration may allow for regulating ATP production and use by bypassing the inhibition of OXPHOS .…”
Section: Resultsmentioning
confidence: 99%
“…ATP and ADP were measured based on steady-state levels, rather than ADP phosphorylation. 68 However, the compensatory mechanism of mitochondrial respiration may allow for regulating ATP production and use by bypassing the inhibition of OXPHOS. 67 Although the OXPHOS intermediates NADH, NADPH, and fumarate were below the detection limits, the results of Mito-RETC complex activity (Figures 2D−H) provide evidence that OXPHOS was strongly affected by DR-MoS 2 .…”
Section: Effect Of Df-mos 2 Dr-mos 2 and Molybdate On Cellular Acti...mentioning
confidence: 99%
“…Indeed, chemicals may impact chemosensory behavior controlling the C. elegans ability to be attracted or avoid certain natural products. For example, we have recently shown that a sublethal dose of silver nanoparticles can completely block the C. elegans ability to be attracted to a food-like odor ( 80 ). Contributing to this idea is the fact that rotenone is also well known for causing neurotoxic effects ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human mitochondrial dysfunction is further complicated by evidence that genetic mutations can enhance mitochondrial toxicity suggesting there are unidentified environmental and pharmacological stressors that cause mitochondrial toxicity in individuals harboring mutant alleles. For example, a recent report using the nematode Caenorhabditis elegans showed that the sublethal concentrations of silver nanoparticles, which are extensively used in consumer products and biomedical applications, alter the development, behavior, and mitochondrial function in worms that harbor genetic defects in mitochondrial dynamics ( 87 ). Furthermore, a recent study demonstrated that exposure to ddC induces mtDNA stress leading to activation of the STING1/TMEM173-mediated DNA sensing pathway and autophagy-dependent ferroptotic cell death ( 88 ).…”
Section: Discussionmentioning
confidence: 99%